2019
DOI: 10.3389/fendo.2019.00551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CPAP on Testosterone Levels in Patients With Obstructive Sleep Apnea: A Meta-Analysis Study

Abstract: Background: Obstructive sleep apnea (OSA) represents a frequent complication among patients with obesity and has been associated with neuroendocrine changes, including hypogonadism. Objective: We conducted a systematic review and meta-analysis to evaluate the effects of continuous positive airway pressure (CPAP) on testosterone and gonadotropins in male patients with OSA. Methods: The review was registered on PROSPERO (CRD42018103164). PubMed, Scopus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…Discordant findings have been found to date on this topic. Particularly, a body of evidence supports the significant improvements that can be achieved with TT following the management of obesity, either by lifestyle measures, pharmacological therapy or bariatric surgery, while no change in TT has been found in hypogonadal subjects with obstructive sleep apnoea following continuous positive airway pressure (CPAP) 17,80‐82 . The mechanisms and effects of physical exercise in obesity have been recently evaluated by using an animal model of metabolically induced hypogonadism 83 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discordant findings have been found to date on this topic. Particularly, a body of evidence supports the significant improvements that can be achieved with TT following the management of obesity, either by lifestyle measures, pharmacological therapy or bariatric surgery, while no change in TT has been found in hypogonadal subjects with obstructive sleep apnoea following continuous positive airway pressure (CPAP) 17,80‐82 . The mechanisms and effects of physical exercise in obesity have been recently evaluated by using an animal model of metabolically induced hypogonadism 83 .…”
Section: Resultsmentioning
confidence: 99%
“…TT has been found in hypogonadal subjects with obstructive sleep apnoea following continuous positive airway pressure (CPAP). 17,[80][81][82] The mechanisms and effects of physical exercise in obesity have been recently evaluated by using an animal model of metabolically induced hypogonadism. 83 It should be noted that, despite positive results, high failure rates have been reported for interventions targeting obesity, especially when treatment is discontinued; weight is regained, and a worsening of hypogonadism has to be expected in these patients.…”
Section: Should Testosterone Replacement Therapy Be Considered As Tmentioning
confidence: 99%
“…Some studies have demonstrated that CPAP elevates testosterone levels (49,50). However, the majority of other studies, including two meta-analyses, have reached a different conclusion (51,52). As pointed out by one of the latest systematic reviews, a small number of included studies in their meta-analysis reported an adequate CPAP use (4 h per night on at least 70% of nights), and thus the results might reflect, at least in part, suboptimal CPAP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have evaluated the sexual health status and the effects of CPAP treatment in men with OSAS. Cignarelli [15] et al reported that in males with OSAS, there was a correlation between disease severity and sexual dysfunction. The authors also reported an improvement in the negative impact of these conditions on quality of life after CPAP treatment.…”
Section: Discussionmentioning
confidence: 99%